Strengthening Notary Reporting Obligations to Prevent Money Laundering in Property Transactions - Titin Hartati; KMS Herman (Yayasan Cendekia Gagayunan Indonesia, 2025)
Money laundering through property transactions poses a significant threat to Indonesia’s legal system and economic integrity due to the high value and complex nature of real estate dealings. Notaries, as public officials authorized to draft authentic deeds and verify legal transactions, occupy a strategic position in detecting and preventing money laundering activities. This study aims to analyze the role of notaries in preventing money laundering in property transactions through the reformulation of reporting obligations. The research employs a normative legal method using statutory and conceptual approaches by examining Law Number 8 of 2010 on the Prevention and Eradication of Money Laundering, Law Number 2 of 2014 on the Position of Notaries, and PPATK Regulation Number 3 of 2021 concerning reporting procedures for certain professions. The findings reveal that although the legal framework clearly establishes notaries as reporting parties, implementation remains ineffective due to internal obstacles such as limited technical understanding and conflicts with professional secrecy, as well as external obstacles including weak coordination with PPATK and insufficient legal protection for reporting notaries. This study concludes that reformulating reporting obligations is necessary through clearer normative positioning of notaries, simplified and digitized reporting mechanisms, strengthened legal protection, and continuous professional training. Optimizing these aspects will enhance the preventive function of notaries and significantly contribute to national efforts to combat money laundering in the property sector.